Study on the Tribological Properties of Porous Titanium Sliding against Tungsten Carbide YG6 - Zhiqiang Liu (Metals, 2017)
In the metal cutting process, the friction and wear behavior between the cutting tool and machined surface is the most important factor that affects the surface quality and the service life of the cutter. The irregular pore structure of porous titanium alloy has changed its mechanical properties and the processing technology. The friction and wear mechanism of the cutting tool and the machined surface is greatly different from the traditional dense metal processing because of the crumbling at the edges, tearing phenomenon and the pore agglomeration effect of chips. In this paper, the tribological characteristics and the wear mechanism of friction pair which was formed by porous titanium alloy material and hard alloy cutter were studied from cutting force, cutting speed and temperature in micro-cutting condition, and the influence of porosity on the wear rate and friction coefficient was analyzed. Results show that the main factor which influences the friction coefficient and wear rate is the porosity. The wear mechanisms of porous titanium materials were abrasive and oxidation wear while the wear mechanism of tungsten carbide YG6 was abrasive wear. The friction coefficient and wear rate of the relatively stable state are beneficial to improve the surface quality and tool life. As a result, in the micro-cutting process of porous titanium alloys, the best choice of machining parameters for different porosity materials are as follows: the load is about 8 N, the sliding speed is about 400 r/min and the temperature is about 300 °C.